Poetics of Impressionism in the French and Russian Lyrics of the Late XIX - Early XX Centuries (based on the Work of P. Verlaine and M. Voloshin) - A. L. Latukhina; Y. A. Marinina (Научный диалог, 2018)
The issues of interaction between impressionism and symbolism in French and Russian poetry of the late XIX - early XX centuries are considered. In the work of Paul Verlaine, the manifestation of such features of impressionism as the image of the fusion of man and nature (subject and object of the image), attention to the shades of feelings and moods, suggestiveness, synesthesia, musicality is shown. It is proved that, along with these features, mythological allusions, references to other cultural epochs and the desire for universality testify to the symbolist tendencies in his work. The authors come to the conclusion that the combination of impressionism and symbolism is also found in the genre of the “landscape of the soul”, authored by Verlaine. It is noted that M. Voloshin became a follower of Verlaine in Russian poetry. The problem of the influence of French poetry on Russian literature of the early twentieth century, in particular, on the work of M. Voloshin, is studied. The authors consider the theoretical works of the poet himself, in which he comprehends the synthesis of symbolism and impressionism in French literature, defining a new type of artistic consciousness “neo-realism”, and cycles of poems “Cimmerian Twilight” and “Cimmerian Spring”, in which tendencies of symbolic-impressionistic poetics are revealed.